Analisis Pengaruh Atribut Iklan Televisi terhadap Ekuitas Merek - Muhamad Ali Sukrajap (Universitas Proklamasi 45 Yogyakarta, 2013)
The corporate world has level changes very quickly. It is no wonder that the producers are vying to sell their products in order to quickly sell at the market. Frequently used media channels are through advertising. One of the kind advertising are television commercials. The making of television advertising must be pleasing consumers, meaning that in designing the ads need to pay attention to the ad attribute in order to make consumers interested in finding out more about the product and brand preference of the planting efforts in the minds consumers. Television advertising is one way to manage a good brand equity. This study aims to measure the extent of the influence of television advertising in the attribute of ad Sprite version